Gender Representation in the Division of Domestic and Public Roles in Modern Families in Surabaya - Wulan, Nawang; Ridwan, Ahmad; Fauzi, Agus Machfud; Ambarwati, Maha Dewi (Journal of Family Sciences, 2025)
Gender inequality in domestic and emotional responsibilities remained strongly embedded in modern families. This study aimed to examine how domestic and emotional roles were represented and negotiated in dual-income families in Surabaya. A descriptive qualitative approach was employed, involving five urban families selected through purposive sampling. Data were collected over three months through semi-structured interviews and participatory observation. The results indicated that domestic and emotional work was still dominated by women, with primary responsibilities largely assigned to them, while men’s involvement tended to be occasional and was socially perceived as voluntary. Subtle resistance strategies adopted by women, such as delaying housework or involving their sons, rarely led to sustained changes in the division of labor. The study concluded that efforts toward gender equality in the domestic sphere required gender-responsive policies, expanded paternity leave, and early gender equality education. These measures were essential to encourage men’s active participation in household labor and to foster more egalitarian family relationships.